(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The new generation of feminism embraces beauty and power of women’ssexuality to achieve their needs. They consider sexual pleasure a human right.Many writers in India have talked of pleasure and its manifestations. Theheroines in Ms. De’s novels rebuild their lost fortunes; make all efforts tolook glamorous by losing weight and spending money in massage parlours. Theytry to look and act differently from the conventional and traditional women.They love to fall in love with their looks by which they try to attract people.It gives them immense pleasure when people fall head to heels in love with themand they are least concerned about it. Shobha De’s doesn’t believe in describing her women characters as loveslaves or mere help mates at home. Shobha De as a writer tries to mirror orportray her feminist mindset while portraying women in her novels. A broaderevaluation of her work reveals her protest against the good old image of womenwho can’t live the way she wants to and do things the way she wants to.